Transformation mechanisms from metallic Zn nanocrystals to insulating ZnSiO3 nanocrystals in a SiO2 matrix due to thermal treatment - Yuk, J. M.; Lee, J. Y.; No, Y. S.; Kim, T. W.; Choi, W. K. (AMER INST PHYSICS, 2008)
Transmission electron microscopy (TEM), high-resolution TEM, and x-ray energy dispersive spectroscopy results showed that Zn metallic nanocrystals and ZnSiO3 insulating nanocrytals embedded in a SiO2 matrix were created from the ZnO thin films deposited on n-Si (001) substrates due to rapid thermal annealing. The formed Zn metallic nanocrystals were transformed into monoclinic ZnSiO3 insulating nanocrystals with increasing number of Zn atoms resulting from an increase in the annealing time up to 10 min. The transformation mechanisms from metallic Zn nanocrystals to insulating ZnSiO3 nanocrystals in a SiO2 matrix due to rapid thermal annealing are described on the basis of the experimental results.
Keywords: SILICON NANOCRYSTALS; TEMPERATURE; GROWTH; FILMS